2021
DOI: 10.3390/atmos12030298
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Mesoscale Model GRAMM-SCI: Evaluation of Simulated Highly-Resolved Flow Fields in an Alpine and Pre-Alpine Region

Abstract: In this study, new developments implemented in the mesoscale model GRAMM-SCI are presented. GRAMM-SCI has been specifically developed for providing flow fields in the sub-kilometer range. A comprehensive model evaluation using wind, temperature, radiation, as well as soil moisture and soil temperature observations in an alpine valley and in a hilly pre-alpine region in Styria (Austria) is presented. Three one-way nested model domains were used, whereby the coarse model run (5000 m horizontal resolution) was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Overall, most model evaluation studies are restricted to readily available quantities such as specific humidity, radiation, wind, and temperature (Tomasi et al 2017;Jiménez-Esteve et al 2018). A number of studies have evaluated the performance of mesoscale models in simulating flow fields in the Alps (Giovannini et al 2014;Gsella et al 2014;Cantelli et al 2017;Schmidli et al 2018;Schlager et al 2019;Oettl 2021a), but comparisons with observations of all surface-energy fluxes are still scarce in the scientific literature (one exception being Sun et al 2017), especially in mountainous terrain and with respect to small-scale spatial variations. The above studies have highlighted some challenges in simulating the near-surface atmosphere over mountainous terrain.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, most model evaluation studies are restricted to readily available quantities such as specific humidity, radiation, wind, and temperature (Tomasi et al 2017;Jiménez-Esteve et al 2018). A number of studies have evaluated the performance of mesoscale models in simulating flow fields in the Alps (Giovannini et al 2014;Gsella et al 2014;Cantelli et al 2017;Schmidli et al 2018;Schlager et al 2019;Oettl 2021a), but comparisons with observations of all surface-energy fluxes are still scarce in the scientific literature (one exception being Sun et al 2017), especially in mountainous terrain and with respect to small-scale spatial variations. The above studies have highlighted some challenges in simulating the near-surface atmosphere over mountainous terrain.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of GRAMM-SCI and WRF for an Alpine valley is crucial to resolve small-scale wind structures (Jiménez-Esteve et al 2018;Schmidli et al 2018;Schlager et al 2019;Oettl 2021a), processes impacting the surface-energy budget components, such as topographic shading (Schlager et al 2019), surface albedo (Tomasi et al 2017), and land-use class (Jiménez-Esteve et al 2018), have equally been identified as strongly impacting the modeled near-surface temperature and wind fields. Understanding model deficiencies in reproducing observed surface radiation, sensible, and latent heat fluxes over mountainous terrain is thus paramount to further improve numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2018 ; Schlager et al. 2019 ; Oettl 2021 ), but comparisons with observations of all surface-energy fluxes are still scarce in the scientific literature (one exception being Sun et al. 2017 ), especially in mountainous terrain and with respect to small-scale spatial variations.…”
Section: Introductionmentioning
confidence: 99%